Report of the Asian Population Conference. And selected papers. (Held at New Delhi, India, 10-20 December, 1963). [Forew. by U Nyun] (United Nations, 1964)
Economic Commission for Asia and the Far East. Bangkok, Thailand. United Nations Publication.